Case concerning sovereignty over Pulau Batu Puteh: a critical analysis of its legal implications - Hamid, Abdul Ghafur@Khin Maung Sein (LexisNexis, 2011)
The International Court of Justice in the case concerning sovereignty over Pedra Branca/Pulau Batu Puteh adjudged Pedra Branca/Pulau Batu Puteh to Singapore, Middle Rocks to Malaysia, and South Ledge to the state in the territorial waters of which it is located. The judgment has far-reaching implications for both Malaysia and Singapore as it creates overlapping territorial waters, leaving sovereign rights of the two states unresolved, in an area which is strategically extremely important. The present paper ﬁrst of all gives a brief commentary on the judgment and identiﬁes issues that may arise in its implementation. The paper touches upon the issue of whether an exclusive economic zone can be claimed from Pedra Branca and suggests that the best solution is to concentrate on the territorial sea delimitation rather than claiming wider maritime zones. On other maritime features, since Middle Rocks, which is under the Malaysian sovereignty, lies in between Pedra Branca and South Ledge and blocks any expansion of territorial waters from Pedra Branca, the paper argues that South Ledge squarely falls within the territorial waters of Malaysia and Malaysia can take South Ledge as a base point for maritime delimitation. To tackle maritime delimitation and other related issues will deﬁnitely require close cooperation and mutual understanding between the two neighbours.